THE IMPACT OF RELIGION ON PREVENTING TRAFFICKING IN HUMAN BEINGS IN KOSOVO (Religious dialogue and cooperation, 2021)
The article addresses the phenomenon of trafficking withhuman beings, focusing specifically on the religious componentof preventing this phenomenon. To study this phenomenon, it isnecessary to study the causes of human trafficking in Kosovo from areligious point of view. Concerning this negative phenomenon whichhas also spread at a global level, Kosovo, as a new and developingstate, has built legal infrastructure for the prevention, protection,treatment and reintegration of victims of human trafficking inKosovo. The functioning of the above is being carefully considered.The research question is: How does religion impact the preventionof trafficking in human beings in Kosovo? Relevant literature thathas dealt with this phenomenon from a religious perspective is usedfor this theme in the study. To study this phenomenon, knowledgeand factual data are used on the history of the development of thisphenomenon. Factual data coming from relevant institutions inKosovo (dealing with this phenomenon in Kosovo) is used to evaluateand measure the effectiveness of preventing human trafficking inKosovo. The methodology used for the study of the phenomenonwill focus on the methods: deductive, historical, statistical,comparative, etc. Secondary data are used for assessments andmeasurements of the development of the phenomenon, which willbe obtained from relevant institutions of Kosovo. From the dataand assessments on the development of the phenomenon resultswill be drawn on the effectiveness of the functioning and impactof the religious system on prevention of trafficking in humanbeings in Kosovo. We find that religion contributes to the raising ofconsciousness and morality of the people, and it exposes the uglyactivity of trafficking in human beings in Kosovo. Overall, we findthat families at risk of trafficking in human beings in Kosovo havea low standard of living, and Social schemes currently operating inKosovo are not sufficient to cover all social categories that needsocial assistance.
Keywords: human victims; trafficking in human beings; traffickers; prevention; treatment; reintegration; social schemes; protection; services; punishment; religeous education